Pengaruh Gaya Mengajar Latihan Dan Gaya Mengajar Komando Terhadap Hasil Belajar Lempar Lembing Pada Mahasiswa Jurusan Pendidikan Olahraga - Jes Jemmy Mangindaan (Peneliti.net, 2022)
This study aims to examine the application of the exercise teaching style and the commando teaching style to the improvement of the javelin-throwing learning outcomes for the students of the Department of Sports Education. The method used in this research is the experimental method. The research design used was a randomized two group pre-test and post-test design. The instrument used in this study was the javelin throwing ability test. The data collection technique in this study was to conduct a preliminary test and a final test of the javelin throwing ability for both groups. From the calculation of the research hypothesis testing, it is obtained that tcount is 1.30. Based on the t distribution table at 0.05 with degrees of freedom n1 + n2 - 2 = 10 + 10 – 2 = 18, the t table is 2.101. So tcount is smaller than ttable, namely tcount = 1.30 ttable = 2.101. Based on the test criteria, if tcount is smaller than ttable (tcount table), then accept Ho, which means HA is rejected. Thus, the conclusion of the test is that the average increase in javelin-throwing skill learning outcomes in the experimental group (X1) which is taught using the Exercise teaching style is the same as the average increase in the javelin-throwing skill in the experimental group (X2) which is taught using the commando teaching style.